Blood metabolite concentrations during pregnancy and postpartum in Akkaraman ewes - Balikci, E.; Yildiz, A.; Gurdogan, F. (Elsevier, 2007)
The aim of this study was to investigate the serum glucose, cholesterol, total protein, albumin, globulin, urea and bilirubin concentrations in Akkaraman ewes at 60, 100 and 150 days of pregnancy and 45 days postpartum. All blood profiles were determined in 30 healthy pregnant Akkaraman sheep with single or twin lambs. While serum glucose, total protein and globulin levels were lower (P < 0.05), serum cholesterol and triglyceride levels were higher (P < 0.05) in twin-bearing sheep, compared to single-bearing sheep on days 100 and 150 of pregnancy. Lower (P < 0.001) serum glucose levels were recorded on day 100 and 150 of pregnancy, compared to day 45 postpartum and day 60 of pregnancy in both groups of ewes. Lower (P < 0.01) serum total protein and globulin levels were recorded on day 150 of pregnancy than at any other stages of gestation in both groups. When compared to day 45 postpartum in groups with twins and singletons, a gradual increase (P < 0.001) in serum cholesterol (78.8 and 83.1 mg/dl, respectively) and triglyceride levels (28.6 and 32.7 mg/dl, respectively) was recorded during pregnancy. Serum urea levels increased (P < 0.05) on days 60 and 100 of pregnancy (28.5, 28.0 mg/dl and 27.0, 26.8 mg/dl in singletons and twins, respectively), compared with day 150 of pregnancy and day 45 postpartum in both groups. Blood glucose, total protein, globulin and urea levels decreased, while the cholesterol, triglyceride and bilirubin increased, especially at 100 and 150 days of pregnancy. The magnitude of changes was greater in twin-bearing sheep, which could be attributed to increased nutrient demands of the multiple fetuses. (c) 2005 Elsevier B.V All rights reserved.
Keywords: blood metabolite; pregnancy; lactation; ewes